2016
DOI: 10.1177/1525822x16639015
|View full text |Cite
|
Sign up to set email alerts
|

How Many Focus Groups Are Enough? Building an Evidence Base for Nonprobability Sample Sizes

Abstract: Few empirical studies exist to guide researchers in determining the number of focus groups necessary for a research study. The analyses described here provide foundational evidence to help researchers in this regard. We conducted a thematic analysis of 40 focus groups on health-seeking behaviors of African American men in Durham, North Carolina. Our analyses revealed that more than 80% of all themes were discoverable within two to three focus groups, and 90% were discoverable within three to six focus groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
669
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(774 citation statements)
references
References 32 publications
28
669
0
5
Order By: Relevance
“…Due to the rapid nature of this technique and the intention to gather preliminary consumer‐generated terminology rapidly for further steps in the research process, only three groups where conducted. Guest, Namey & Mckenna () states that when conducting three focus groups, about 80 to 90% of the information can be discoverable. Those authors also mentioned that three focus groups were “enough to identify all of the most prevalent themes within the data set.” The participants were all female, and there were seven participants in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the rapid nature of this technique and the intention to gather preliminary consumer‐generated terminology rapidly for further steps in the research process, only three groups where conducted. Guest, Namey & Mckenna () states that when conducting three focus groups, about 80 to 90% of the information can be discoverable. Those authors also mentioned that three focus groups were “enough to identify all of the most prevalent themes within the data set.” The participants were all female, and there were seven participants in each group.…”
Section: Methodsmentioning
confidence: 99%
“…First, four focus groups comprising 41 participants were conducted. Previous research has suggested that 80% of all themes can be identified in two to three focus groups (Guest et al, 2016). Second, we systematically sampled first, second, and third year students respectively from one degree for the first three focus groups to ensure we could identify possible similarities and differences across cohorts, and followed this with a focus group comprising students from varying degrees and years.…”
Section: Methodsmentioning
confidence: 99%
“…We elicited participants through email, brief presentations at staff meetings, flyers, and word of mouth with a target sample size of two to four focus groups and/or individual interviews per profession or until saturation of the data was achieved. Two to four focus groups has been shown to reliably achieve data saturation in previous research . We sought a total of 30 to 35 participants (approximately 8%–10% of the total eligible subjects) to capture the diverse role‐based experiences of staff.…”
Section: Methodsmentioning
confidence: 99%